Life Cycle Assessment of Organic Waste Pellet for Sustainable Energy Production in IPB University Campus - Sri Mulyani; Edy Hartulistiyoso; Supriyanto Supriyanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The growing population and improving living standards are resulting in higher demand for energy and materials. Renewable energy addresses this challenge while reducing greenhouse gas emissions. Organic waste has significant potential to be converted into pellet-based renewable energy, but sustainable production is essential to minimize environmental impact. This study aims to evaluate the environmental impact using a life cycle assessment with 5 categories, namely Global Warming Potential (GWP), Stratospheric Ozone Depletion (SOD), Terrestrial Acidification (TAC), Freshwater Eutrophication (FEU), and Human Carcinogenic Toxicity (HCT) for each pellet. The results of twig and leaf pellets were, respectively, GWP of 3.05 kg CO2-eq and 0.54 kg CO2-eq; SOD of 1.6×10–6 kg CFC11 eq and 1.35×10–7 kg CFC11-eq; TAC of 0.0131 kg SO2-eq and 0.0018 kg SO2-eq; FEU of 0.0059 kg P-eq and 0.0006; HCT 0.538 kg 1.4-DCB-eq and 0.0130 kg 1.4-DCB-eq. Based on the result, the production of twig pellets has a higher environmental impact than that of leaf pellets. However, when compared to conventional fuels, the impact caused by twig pellets is still within acceptable limits and is comparatively lower.